Development of In Situ Self-Assembly Nanoparticles to Encapsulate Lopinavir and Ritonavir for Long-Acting Subcutaneous Injection - Irin Tanaudommongkon; Asama Tanaudommongkon; Xiaowei Dong (MDPI AG, 2021)
Most antiretroviral medications for human immunodeficiency virus treatment and prevention require high levels of patient adherence, such that medications need to be administered daily without missing doses. Here, a long-acting subcutaneous injection of lopinavir (LPV) in combination with ritonavir (RTV) using in situ self-assembly nanoparticles (ISNPs) was developed to potentially overcome adherence barriers. The ISNP approach can improve the pharmacokinetic profiles of the drugs. The ISNPs were characterized in terms of particle size, drug entrapment efficiency, drug loading, in vitro release study, and in vivo pharmacokinetic study. LPV/RTV ISNPs were 167.8 nm in size, with a polydispersity index of less than 0.35. The entrapment efficiency was over 98% for both LPV and RTV, with drug loadings of 25% LPV and 6.3% RTV. A slow release rate of LPV was observed at about 20% on day 5, followed by a sustained release beyond 14 days. RTV released faster than LPV in the first 5 days and slower than LPV thereafter. LPV trough concentration remained above 160 ng/mL and RTV trough concentration was above 50 ng/mL after 6 days with one subcutaneous injection. Overall, the ISNP-based LPV/RTV injection showed sustained release profiles in both in vitro and in vivo studies.